Spontaneous anterior dislocation of lens in a case of ectopia lentis et pupillae: a rare entity treated by a novel technique of microscope integrated optical coherence tomography (MIOCT) guided intralenticular lens aspiration - Sahay, Pranita (BMJ Case Rep, 2019)
A 7-year-old girl presented with watering and redness in the left eye for 2 months. Her parents reported poor vision in both eyes for 4 years. Visual acuity was finger counting at 1 m and finger counting close to face in the right and left eyes, respectively. Slit lamp examination of the right eye revealed corectopia, aphakia in the pupillary area, temporally subluxated clear crystalline lens, persistent pupillary membrane, irido-hyaloidal adhesion and poorly dilating pupil. Left eye revealed central corneal oedema with descemet scarring, anteriorly dislocated clear crystalline lens with lenticulo-corneal touch. Ultrasound examination of the left eye was normal. Hence a diagnosis of ectopia lentis et pupillae with left eye spontaneous anterior dislocation of the lens along with corneal decompensation was made. The child underwent microscope integrated intraoperative optical coherence tomography guided intralenticular lens aspiration with optical iridectomy in the left eye. Postoperative visual rehabilitation was done with aphakic glasses.